2016
DOI: 10.1007/s11255-015-1211-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional results of aspiration and sclerotherapy with ethanol in patients with autosomal dominant polycystic kidney disease: a non-randomized pilot clinical study

Abstract: Aspiration and sclerotherapy with ethanol is a minimal-invasive, safe, and inexpensive outpatient treatment method with acceptable short- and long-term results in ADPKD patients. Aspiration and sclerotherapy with ethanol can be an option for patients with ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…13 Mechanical cyst reduction strategies, such as cyst aspiration and sclerosis with ethanol or laparoscopic cyst decortication, have been used for decades in an effort to relieve the pain associated with large cysts and/or large kidneys, with success rates for pain relief varying from 25% to 100% and follow-up ranging from 12 months to more than 10 years. [14][15][16][17] Similarly, among the 41 patients in the present study who reported symptoms due to mass effect of the large kidneys, w70% experienced improvement in their symptoms. Adverse events occurred, comprising postprocedure pain in 9 patients (lasting for >1 month in 2), 1 potential and 2 definite procedurerelated cyst infections, and asymptomatic intermittent hematuria for several days in 1 patient.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…13 Mechanical cyst reduction strategies, such as cyst aspiration and sclerosis with ethanol or laparoscopic cyst decortication, have been used for decades in an effort to relieve the pain associated with large cysts and/or large kidneys, with success rates for pain relief varying from 25% to 100% and follow-up ranging from 12 months to more than 10 years. [14][15][16][17] Similarly, among the 41 patients in the present study who reported symptoms due to mass effect of the large kidneys, w70% experienced improvement in their symptoms. Adverse events occurred, comprising postprocedure pain in 9 patients (lasting for >1 month in 2), 1 potential and 2 definite procedurerelated cyst infections, and asymptomatic intermittent hematuria for several days in 1 patient.…”
supporting
confidence: 63%
“…All older studies, as well as the the present cohort study, were observational and underpowered to determine long-term effects on kidney function, but the general conclusion was that mechanical cyst reduction had no detrimental but also no beneficial effect on progression to ESKD. [14][15][16][17] Why does reduction of total kidney volume by cyst aspiration not lead to improvement in kidney function in this and the older studies? One obvious reason is that only a few cysts among hundreds to thousands can be targeted by foam sclerotherapy.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Current management strategies include blood pressure control (commonly achieved by administering medications that interact with the renin-angiotensin-aldosterone pathway) and minimization of nephrotoxin exposure (18). Symptomatic dominant cysts have been treated successfully with image-guided aspiration and ethanol sclerotherapy (also known as ethanol sclerosis), with excellent long-term outcomes (19).…”
Section: Hereditary Renal Cystic Disorders and Their Key Featuresmentioning
confidence: 99%
“…A variety of therapeutic interventions have been described for benign symptomatic cystic lesions of the kidney. These include cyst aspiration 5 , surgical resection 6 , 7 , and sclerotherapy with a variety of different agents 8 , 9 . Although none of these approaches appear to be better than the others described, aspiration and sclerotherapy are associated with a higher incidence of cyst recurrence, fever, and ureteropelvic junction obstruction regarding the treatment of peripelvic cysts, given their proximity to the renal vessels and collecting system.…”
Section: Introductionmentioning
confidence: 99%